Risk factors for ovarian cancer in Yaounde: A case control study. Issue 3 (2020) - Belinga, Etienne; Koh, Valère Mve; Um, Esther Juliette Ngo; Kalbassou, Fabien; Tompeen, Isidore; Mbala, Peter; Foumane, Pascal
No abstract available